Tanggung Jawab Sosial Perusahaan Bukan Sumber Daya Alam dalam Perspektif ISO 26000 - Yuman Nur Rozak (Universitas Islam Indonesia, 2021)
This study analyzes first, how is the regulation of CSR in Indonesia in accordance with ISO 26000? Second, how should the regulations and CSR formulations address the legal vacuum of non-natural resource companies in Indonesia? This research uses normative juridical method. The results of this study conclude that first, that the regulation of CSR in Indonesia is not in accordance with the regulations contained in ISO 26000. CSR regulations in Indonesia are still scattered in several laws and regulations. Non-natural resource companies are not required to carry out CSR even though their business activities have a major impact on the social and environmental environment. Second, there is a need for special regulations that regulate the implementation and mechanism for implementing CSR in Indonesia in an integrated and codified manner. The regulation of CSR in Indonesia needs to be reformulated by adopting the principles of CSR implementation contained in ISO 26000, in the form of a law which contains two main provisions, namely the implementation of CSR for natural resources companies and the implementation of CSR for non-natural resources companies.Key Words: CSR; company; ISO 26000; non-natural resources; regulationAbstrakPenelitian ini menganalisis, pertama, apakah pengaturan CSR di Indonesia sudah sesuai dengan ISO 26000? Kedua, bagaimanakah seharusnya regulasi dan formulasi CSR untuk mengatasi kekosongan hukum terhadap perusahaan bukan SDA di Indonesia? Penelitian menggunakan metode yuridis normatif. Hasil kajian ini menyimpulkan, pertama, pengaturan CSR di Indonesia tidak sesuai dengan pengaturan yang terdapat dalam ISO 26000. Regulasi CSR di Indonesia masih tersebar di beberapa peraturan perundang-undangan. Perusahaan bukan SDA tidak diwajibkan untuk melaksanakan CSR meskipun kegiatan usahanya sangat berdampak pada lingkungan sosial dan lingkungan hidup. Kedua, perlu adanya regulasi secara khusus yang mengatur implementasi dan mekanisme pelaksanaan CSR di Indonesia secara terpadu dan terkodifikasi. Pengaturan CSR di Indonesia perlu diformulasikan ulang dengan mengadopsi prinsip-prinsip pelaksanaan CSR yang terdapat dalam ISO 26000, dalam bentuk Undang-Undang yang di dalamnya memuat dua ketentuan utama yakni pelaksanaan CSR bagi perusahaan SDA dan pelaksanaan CSR bagi perusahaan bukan SDA.Kata Kunci: CSR; perusahaan; bukan SDA; ISO 26000; peraturan